MODERN POSSIBILITIES OF THE DIET THERAPY FOR THE PREVENTION AND CORRECTION OF THE CALCIUM DEFICIENCY AMONG INFANTS - N.E. Sannikova; O.V. Stennikova (Вопросы современной педиатрии, 2007)
The work studies the efficiency of the specialized milk formula inclusion into the diet to prevent and correct the calcium deficiency among infants (aged between 1 and 3 years old). The authors discovered the positive impact of the milk formula on the values of the phosphoric and calcic exchange: the level of the ionized calcium, daily excretion of calcium with urine, osteocalcin. They identified the significant effect of the diet therapy for the prevention of the pathologic symptoms on the part of the musculoskeletal system (bearing disorder, reduction of the muscular tonus and etc.).Key words: children, milk formula, calcium, exchange, diet therapy.